Piranesi, the “Egyptian style” and “small architecture”: A synthesis on the inventive multiplicity of the craftsma - Rodrigues, Angela Rosch (Anais do Museu Paulista: História e Cultura Material, 2024)
This article presents a relevant topic in the trajectory of Giambattista Piranesi: the proposition of the “Egyptian style” in the publication Diverse maniere d’adornare i cammini (1769), which reveals some relevant aspects of the Piranesian critical fortune for architectural debates in the 18th century. Firstly, one can gauge Giambattista’s perception of the iconographic and compositional potential of Ancient Egypt by references found in Rome and through the field of decoration, in composing fireplaces — an element of “small architecture.” Its merit lies in presenting a new assessment on the applicability of Egyptian iconography. Additionally, Piranesi attempted to show a way of conceiving the art of building based on variations learned from the lexicon of the Ancients, expressing the craftsman’s ingenuity. This article concludes that by proposing the composition of fireplaces in the “Egyptian style,” Piranesi tested his assumptions about the craftsman’s ability to distribute ornamentation according to the architecture. He thus intended to legitimize, on a theoretical and practical level, a reconciliation between the ancient precepts and the demands of the inventive procedure. Diverse maniere has established itself as a crucial work for understanding Piranesi’s artistic trajectory, consolidating arguments about inventive license based on the repertoire of Antiquity.